PENGARUH INVESTMENT OPPORTUNITY SET DAN FREE CASH FLOW PADA KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN - Suartawan, I Gusti Ngurah Putu Adi; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This research is aimed to determine the effect of investment opportunity set and free cash flow on dividend policy and its impact in manufacturers value. 25 manufacturers is taken as sample on this research, by using purposive sampling method. Data is collected through non participant observation. Path analysis is used as data analysis technique which is an extension of the multiple linear regression technique. Based on the results of analysis, found that: 1) Investment opportunity set has a positive effect on dividend policy, refuse the negative hypothesis; 2) Free cash flow has a positive effect on dividend policy; 3) Investment opportunity set has a positive effect on firm value; 4) Free cash flow has a positive effect on firm value; 5) Dividend policy has a positive effect on firm value; 6) Investment opportunity set has effect on firm value through dividend policy; and 7) Free cash flow has no effect on firm value through dividend policy.
Keywords: firm value, investment opportunity set, free cash flow, dividend policy